Macro and trace elements in edible mushrooms, Shiitake, Shimeji and Cardoncello from Petrópolis, Rio de Janeiro, Brazil - Gonçalves,Jaylei Monteiro (2014)
The concentrations of twenty-five elements (Al, As, Ba, Bi, Ca, Cd, Cr, Cu, Fe, Ga, K, Li, Mg, Mn, Mo, Na, Ni, Pb, Rb , Sb, Se, Sn, Sr, V and Zn) were determined in three edible mushrooms, Shiitake (Lentinula edodes), Black Shimeji (Pleurotus ostreatusi) and Cardoncello (Pleurotus eryngyii) from Petrópolis, Rio de Janeiro, Brazil. Samples were collected along the year 2010 and their preparations were made after drying, milling, an acid pre-digestion and a decomposition procedure in a muffle furnace. The analytical techniques employed for the elements determination were Mass Spectrometry with Inductively Coupled Plasma and Flame Atomic Absorption Spectrometry. Two certified reference materials, Apple Leaves and Mussel Tissue, were used for the evaluation of the analytical procedure and recovery values around 98% were obtained. The results showed that the analyzed mushrooms have high levels of Cu, Fe, K, Mg, Mn and Zn containing more than 30% the recommended daily intake for these nutrients according to Brazilian legislation. These mushrooms presented a very low ratio Na/K. Regarding the levels of some contaminants, the mushrooms had concentrations of Cd, Pb and As below the recommended maximum limits allowed by Brazilian legislation.